2022
DOI: 10.3389/fpls.2022.844545
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling of Tubby-Like Proteins in Soybean and Roles of the GmTLP8 Gene in Abiotic Stress Responses

Abstract: Tubby-like proteins (TLPs) are transcription factors that are widely present in eukaryotes and generally participate in growth and developmental processes. Using genome databases, a total of 22 putative TLP genes were identified in the soybean genome, and unevenly distributed across 13 chromosomes. Phylogenetic analysis demonstrated that the predicted GmTLP proteins were divided into five groups (I-V). Gene structure, protein motifs, and conserved domains were analyzed to identify differences and common featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…A typical TLP, containing the conserved tubby domain formed with a β-barrel structure consisting of one α-helix and 12 anti-parallel strands, functions as a bipartite transcription regulator ( Carroll et al., 2004 ). In addition to be identified in mice ( Kleyn et al., 1996 ), human ( North et al., 1997 ) and other animals ( Heikenwalder et al., 2001 ; Figlewicz et al., 2004 ), this family was also identified in plants such as rice ( Kou et al., 2009 ), Arabidopsis ( Lai et al., 2004 ), wheat ( Hong et al., 2015 ; Li et al., 2018 ; An et al., 2019 ), apple ( Xu et al., 2016 ), soybean ( Xu et al., 2022 ) and cassava ( Dong et al., 2019 ). The widespread and high conservation of tubby family in eukaryotes suggested the fundamental function of growth and development in animals and plants ( Carroll et al., 2004 ; Wang et al., 2018 ; Devane et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A typical TLP, containing the conserved tubby domain formed with a β-barrel structure consisting of one α-helix and 12 anti-parallel strands, functions as a bipartite transcription regulator ( Carroll et al., 2004 ). In addition to be identified in mice ( Kleyn et al., 1996 ), human ( North et al., 1997 ) and other animals ( Heikenwalder et al., 2001 ; Figlewicz et al., 2004 ), this family was also identified in plants such as rice ( Kou et al., 2009 ), Arabidopsis ( Lai et al., 2004 ), wheat ( Hong et al., 2015 ; Li et al., 2018 ; An et al., 2019 ), apple ( Xu et al., 2016 ), soybean ( Xu et al., 2022 ) and cassava ( Dong et al., 2019 ). The widespread and high conservation of tubby family in eukaryotes suggested the fundamental function of growth and development in animals and plants ( Carroll et al., 2004 ; Wang et al., 2018 ; Devane et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified eight TLP s in woodland strawberry ( F. vesca ). The number of TLP s was significantly less in woodland strawberry than in other diploid plants, such as Arabidopsis (11), rice (14), poplar (11), maize (15), tomato (11), and soybean (22) [ 11 , 15 , 23 , 35 ], and no paired paralogous TLP genes were identified in F. vesca ( Figure 1 ) as has been observed in TLP s in Arabidopsis , rice, and poplar [ 35 ]. Intron/exon structures provide important insights into the evolutionary relationships among members of gene families [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…TLPs have been reported to play important roles in the response to abiotic stress in chickpea, apple, cotton, tomato, cucumber, and soybean [ 15 , 19 , 20 , 22 , 25 , 26 ]. FvTLP s also play a role in the response to multiple types of stress and hormone treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations